Exploring the Direction of Islamic Education Amidst Curriculum Changes and the Onslaught of AI - Badrun Badrun; Samsudin Samsudin; Junaidin Junaidin (Fitrah, 2025)
This study aims to examine the methods and processes for exploring the direction of Islamic education goals amidst curriculum changes and the onslaught of AI. This study uses a library research approach. Library research is a study used to collect information and data using various materials available in libraries, such as documents, books, magazines, and historical stories. The results of the study indicate that Islamic education is able to adapt to current developments and technological advances. The presence of AI and curriculum changes does not cause Islamic education to lose its essence and remains steadfast in upholding its Islamic values. Curriculum changes aim to find the right reference as a foundation for all education, and Islamic education remains able to adapt to all existing changes. The existence of AI can help make it easier for teachers and students to complete school assignments quickly and efficiently, without requiring high costs, providing new innovations, providing 24-hour service, and providing consistent answers. However, it does not rule out the possibility that AI also has disadvantages such as unemployment, privacy violations, data security, and technological dependence.